ANALISIS YURIDIS GUGURNYA RESTORATIVE JUSTICE DALAM PROSES PENYIDIKAN TERHADAP PELAKU TINDAK PIDANA PENGANIAYAAN BERAT (LP/B/01/I/2023/POLSEK-KEMPAS/ POLRES.INHIL/POLDA.RIAU) - Siswanto, Alen; Wahyuni, Fitri; Rahmah, Siti (Lembaga Marwah Rakyat, 2024)
The failure of restorative justice in the process of investigating perpetrators of serious crimes (LP/B/01/I/2023/Polsek-Kempas/Polres Inhil/Polda Riau, that the handling of criminal cases of abuse through restorative justice does not yet have a legal basis for implementation according to the case, Settlement of criminal cases of serious abuse through restorative justice is carried out on the basis of police discretion, namely terminating the investigation